A study of coronary artery patency in relation to the index event in patients with myocardial infarction thrombolysed with streptokinase. Issue 1 (28th April 2014) - Gokhroo, R K; Gupta, Sajal; Bisht, Devendra Singh; Padmanabhan, Deepak
Abstract : Background: Restoration of infarct vessel patency is the key treatment for acute ST-elevation myocardial infarction. Objective: The purpose of the study was to confirm the effectiveness of streptokinase (STK) for successful thrombolysis of the infarct-related artery (IRA) in patients with acute myocardial infarction (AMI), in relation to the time of the index event and age compared with newer thrombolytic agents, in a tertiary care centre. Methods: 100 patients (77% male) thrombolysed with STK underwent coronary angiography within 48 h of presentation. Patency of the IRA was used to assess successful thrombolysis. Results: The mean pain-to-needle time was 3.24 h. 76 patients (76%) treated with thrombolysis had patent arteries with thrombolysis in myocardial infarction (TIMI) 2 or 3 flow. In subgroup analysis of time from the index event, patency rates were 83.3%, 77.5%, 68.7% and 40% in patients presenting within 0–2, 2–4, 4–6 and 6–12 h, respectively. In subgroup analysis, all patients less than 30 years of age had patent arteries with TIMI 2 or 3 flow. Coronary angiography showed the IRA was the left anterior descending artery (LAD) in 55%, the right coronary artery (RCA) in 33% and the left circumflex artery (LCX) in 12%. The patency rates of the LAD, RCA and LCX were 74.5%, 69.6% and 100%, respectively. Conclusions: We found STK to be as effective as newer thrombolytic agents reported in other studies. In patients with AMI thrombolysed within 4 h, STK results in higher patency in young compared to older patients.